"Romeo and Juliet: A Love out of the Shell": Using Storytelling to Address Students' Misconceptions and Promote Modeling Competencies in Science - Ginevra Aquilina; Umberto Dello Iacono; Lucia Gabelli; Luca Picariello; Giacomo Scettri; Giulia Termini (MDPI AG, 2024)
In this paper, we present the design of a Teaching-Learning Sequence (TLS) based on storytelling. The TLS has a twofold goal: to address students' misconceptions about atomic models and to promote students' development of modeling skills. The story is titled "Romeo and Juliet: a love out of the shell", and the characters are electrons living inside an atom. The TLS was tested with upper secondary school students. A qualitative analysis of the data shows that the TLS was able to engage students and helped them reconstruct the atomic model, while the story improved students' understanding of specific concepts related to the atomic model. The use of storytelling in the context of our research is discussed, together with the limitations of the story and possible future research developments.